City of light the story of fiber optics - Hecht, Jeff 1947- (The Sloan technology series, 1999)
"City of Light tells the story of fiber optics, tracing its transformation from 19th-century parlor trick into the foundation of our global communications network. Written for a broad audience by a journalist who has covered the field for twenty years, the books is a lively account of both the people and the ideas behind this revolutionary technology."--BOOK JACKET.